Study on Life Style of the Patients of Rheumatic Fever Attending the National Centre for Control of Rheumatic Fever and Heart Diseases (NCCRF/HD) During the Year 1993 to 1996 - Hussain, MA; Nahar, A; Begum, K; Tanira, S (Journal of Dhaka Medical College, 2010)
A Retrospective study was designed to see the status of housing and living environment of the patients of Rheumatic fever. The study was done from January to June 1997 on 477 (Four hundred seventy seven) patients of Rheumatic fever whose data were collected from the records of National Centre for Control of Rheumatic Fever and Heart Diseases (NCCRF/HD), Sher-E-Bangla Nagar, Dhaka. All of them were diagnosed cases of Rheumatic fever of both sexes attended the hospital from the year 1993 to 1996. The study showed that 257 (54%) patients out of 477 came from a family comprising of 7 members or more, 196 (41%) patients from a family comprising of 4-6 members. 50.1% cases resides in kutcha house, 32.9% and 17% cases resides in Pukka and semi-pukka house, respectively. The study shows that 67% of the patients came from the house consisting of 1-2 living rooms, 27.9% from the house consisting of 3-4 rooms. Family comprising of more members, type of residing house especially kutcha house and house consisting of less living rooms increases the incidence of the Rheumatic fever. Key words: Rheumatic fever; Family members; Type of housing and living rooms. DOI: 10.3329/jdmc.v17i2.6579 J Dhaka Med Coll. 2008; 17(2) : 56-58